2012
DOI: 10.1007/s10457-012-9493-9
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid improved tree fallows: harnessing invasive woody legumes for agroforestry

Abstract: For several decades, agroforestry specialists have promoted the planting of fallow fields with nitrogen-fixing, fast-growing trees or shrubs to accelerate soil rehabilitation and provide secondary products like woodfuel. Yet, such 'improved fallows' have not been widely adopted, in part due to the costs of labour and seedlings. In some situations, however, farmers have developed novel approaches to agroforestry fallows by taking advantage of spontaneous invasions of woody leguminous tree species present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Fruit trees and shrubs-from oranges to mangos, from vines to peaches-provide obvious consumable and marketable products, as well as secondary uses of dead branches as fuel wood, and mulberry leaves as silk worm fodder, among many other uses. Other benefits derived from trees include the production of honey based on eucalyptus flowers, the improvement of soil fertility based on acacia nitrogen fixation, and the sale of eucalyptus essential oils [79][80][81]. It is important to note that population growth in Madagascar is still quite rapid, with the country's population doubling between 1990 and 2013.…”
Section: Political Ecological Context Of Tree Cover Changementioning
confidence: 99%
“…Fruit trees and shrubs-from oranges to mangos, from vines to peaches-provide obvious consumable and marketable products, as well as secondary uses of dead branches as fuel wood, and mulberry leaves as silk worm fodder, among many other uses. Other benefits derived from trees include the production of honey based on eucalyptus flowers, the improvement of soil fertility based on acacia nitrogen fixation, and the sale of eucalyptus essential oils [79][80][81]. It is important to note that population growth in Madagascar is still quite rapid, with the country's population doubling between 1990 and 2013.…”
Section: Political Ecological Context Of Tree Cover Changementioning
confidence: 99%
“…Several studies argued that benefits outweigh harms because people have managed harms and created benefits (Dove 1986; Jagoret et al 2012; Tassin et al 2012; Martin 2014; Berget et al 2015). In part this is unsurprising because, depending on the context, ‘Invasions can have positive as well as negative feedbacks for ecosystem functions’ (Vilà et al 2011, p. 702).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these criteria, Tassin, Kull, and Rangan (2012) suggested that the key factors are input costs; labour cost, cash income, multipurpose use and the duration of the fallow. Small farmers fear that costs associated with the new technology outweigh the cash benefits it might offer.…”
Section: Discussionmentioning
confidence: 99%